2010
DOI: 10.1128/iai.01314-09
|View full text |Cite
|
Sign up to set email alerts
|

CCR7-Dependent Immunity during Acute Toxoplasma gondii Infection

Abstract: The chemokine receptor CCR7 is a well-established homing receptor for dendritic cells and T cells. Interactions with its ligands, CCL19 and CCL21, facilitate priming of immune responses in lymphoid tissue, yet CCR7-independent immune responses can be generated in the presence of sufficient antigen. In these studies, we investigated the role of CCR7 signaling in the generation of protective immune responses to the intracellular protozoan parasite Toxoplasma gondii. The results demonstrated a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 51 publications
3
57
0
Order By: Relevance
“…Stimulation of dendritic cells with CCR7 ligands induces their production of IL-12 and IL-23, which can drive Th1 and Th17 differentiation, respectively (83). Consistent with our findings, others have also observed that CCR7 expression on T cells is critical to mount an IFN-γ-dependent immune response that is required to clear pathogens (84).…”
Section: Discussionsupporting
confidence: 79%
“…Stimulation of dendritic cells with CCR7 ligands induces their production of IL-12 and IL-23, which can drive Th1 and Th17 differentiation, respectively (83). Consistent with our findings, others have also observed that CCR7 expression on T cells is critical to mount an IFN-γ-dependent immune response that is required to clear pathogens (84).…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the expression of CCR7 in the retina and brain of WT mice increased at day 21 after infection and was sustained even at day 56 after infection, which was in agreement with previous studies investigating the brain and peripheral organs 11 33. On the other hand, in the retina and brain of GKO mice, this molecule stayed at basal level throughout the infection course, indicating that CCR7 expression after T gondii infection was dependent on IFN-γ.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, transcripts encoding both chemokines rise significantly in the CNS following infection of mice with the protozoan parasite, Toxoplasmosis gondii (Noor et al ., 2010). CCR7-deficient mice succumb to disease early in association with increased parasite burden in the brain.…”
Section: Lymphoid Chemokines In Infections Of the Cnsmentioning
confidence: 99%